Hydraulic, textural and geochemical characteristics of the Ajali Formation, Anambra Basin, Nigeria: implication for groundwater quality (2009)
"This study highlights the distribution of hydraulic conductivity (K) in the regional aquiferous Ajali Formation of SE-Nigeria on one hand and assesses the possible influences of textural and geochemical characteristics on the hydraulic conductivity on the other hand. The investigation approach involved field sampling and collection of 12 sandstone samples from different outcrop locations, followed by laboratory studies such as grain-size analysis (GSA), constant head permeameter test and geochemical analysis of major and trace elements using X-ray fluorescence method. GSA and textural studies show that the sandstones range from fine to medium sands, constituting about \75–99% sand fraction, with graphic mean grain size of 0.23–0.53 mm. Other parameters such as coefficient of uniformity (Cu) range from 1.58 to 5.25 (av. 2.75), while standard deviation (sorting) values of 0.56Ø– 1.24Ø imply moderately well sorted materials. In addition, the order of the estimated K values is Kpermeameter>KBeyer>KHazen>KKozeny-Carmen>KFair-Hatch with average values of 1.4˟10-3, 4.4˟10-4, 3.8˟10-4, 2.2˟10-4 and 8.1˟10-5 m/s, respectively. These values fall within the range of 10-5 and 10-3 m/s for fine to medium sands. However, multivariate factor analysis of the data revealed significant positive dependence of the empirically determined K values on graphic mean grain size and percentage sand content and much less dependence on sorting and total porosity. Geochemical profiles of the fresh samples are dominated by quartz with corresponding SiO2 content of 76.1–98.2% (av. 89.7%) while other major oxides are generally below 1.0 wt.% in the fresh samples. However, the ferruginized samples exhibited elevated concentrations of Al2O3 (3.50–11.60 wt.%) and Fe2O3 (1.80–3.60 wt.%), which are clear indications of weathering/ferruginization processes with attendant trace metal release/enrichment (2.5 mg/l Cu, 7.5 mg/l Pb, 6.5 mg/l Zn, 3.9 mg/l Ni and 19.6 mg/l Cr) call for concern in respect of the chemical quality of the groundwater system. The associated groundwater is generally soft, slightly acidic, and with low dissolved solids (EC = 14–134 ls/cm) dominated by silica; implying water from clean sandy aquifer devoid of labile and weatherable minerals. Nonetheless, most of the metals (with exception of Si, Fe and Mn) exhibited higher degree of mobility (2–12 folds), which can be attributed to reduction of Fe-/Mn-oxyhydroxides as sinks/hosts for trace metals. Consequently, infiltration-induced geochemical reactions (redox, ferruginization and leaching processes) signify potential environmental impact in terms of groundwater quality as well as borehole/aquifer management, especially under humid tropical environment of the study area. "